Yigu decoction regulates plasma miRNA in postmenopausal osteoporosis patients: a randomized controlled trial - Chen, Haifeng; Zhang, Ruikun; Li, Guijin; Yan, Kun; Wu, Ziqi; Zhang, Yang; Chen, Zhineng; Yao, Xinmiao (Frontiers in Pharmacology, 2024)
Background Postmenopausal osteoporosis (PMOP) is a serious condition that affects elderly individuals. Our previous study revealed that Yigu decoction (YGD) effectively improved bone mineral density (BMD) in elderly individuals, but the mechanism underlying this effect remains unclear. In this study, we investigated the relationships among YGD, microRNAs (miRNAs), and bone metabolism by assessing the effects of YGD on the miRNA levels in patient plasma to provide a scientific basis for treating PMOP with YGD. Methods In this clinical trial, 60 patients were randomly assigned to the YGD group or the control group (ratio of 1:1) and treated for 3 months. The primary outcome measure was BMD, and the secondary outcome measures included plasma miRNA levels, visual analogue scale (VAS) scores, alkaline phosphatase (ALP) levels, anti-tartrate acid phosphatase (TRACP-5b) levels and traditional Chinese medicine (TCM) syndrome scores. We assessed the regulatory roles of miRNAs in PMOP patients by analysing publicly available data from the Gene Expression Omnibus (GEO) database. Bioinformatics methods were also used to explore the mechanism by which YGD regulates miRNAs that are involved in bone metabolism. Results Compared with those before treatment, the BMD, ALP levels, TRACP-5b levels, TCM syndrome scores and VAS scores improved in both groups after 3 months of treatment (P < 0.05). A total of 82 miRNAs differed between the groups. After analysing data from the GEO database, we confirmed that miR-133a-3p is the key molecule that mediates the effects of YGD intervention on PMOP. GO analysis of key genes suggested that gene enrichment was more pronounced in response to hormones, cellular response to growth factor stimulation, and positive regulation of physiological and metabolic processes. KEGG analysis revealed that these genes were enriched mainly in the PI3K-Akt, FOXO, and JAK-STAT pathways and other pathways. The results of the protein‒protein interaction (PPI) network analysis revealed that epidermal growth factor receptor (EGFR), Insulin-like growth factor 1 (IGF-1), Caveolin-1 (Cav-1) and others were core proteins. Conclusion This study demonstrated that YGD is beneficial in the treatment of PMOP, ameliorating clinical symptoms and bone turnover indices. Moreover, the inhibition of miR-133a-3p expression may be the key mechanisms by which YGD regulates bone metabolism in the treatment of PMOP, although YGD regulates bone metabolism in a multitarget and multipathway manner.